Exploring Teaching Perspectives Embraced by Teachers in Teaching Agricultural Sciences in Secondary Schools in South Africa - Nonhlanhla Fortunate Nduku (E-Journal of Humanities, Arts and Social Sciences)
The South African Curriculum Assessment Policy Statement (CAPS) document stipulates that in teaching Agricultural Sciences (AGRIS), teachers should cement their pedagogical practices in three aspects: knowledge, skill, and values/attitudes. The statement contends for the interwoven prescriptive (knowledge), communal (skills), and habitual (values/attitudes) perspectives, which are apropos of balancing three aspects of teaching AGRIS. The study, therefore, explored teachers’ perspectives when teaching AGRIS in secondary schools. The study was grounded in the Cultural Historical Activity Theory (CHAT), shaped by Vygotsky. From the critical paradigm, the study employed reflective activities, interviews, observations, and focus groups as data generation methods through action research. Six participants were purposefully selected to bring an in-depth understanding of the phenomenon. The findings exhibited that teachers embrace the prescriptive perspective when teaching AGRIS in secondary schools. On the one hand, teachers impart content knowledge during AGRIS teaching. On the other hand, the CAPS document is silent about how teachers should instill skills and values/attitudes in learners. It is recommended that the AGRIS curriculum developers amend the enactment of skills and values/attitudes driven by communal and habitual perspectives. Nonetheless, the researcher calls for aligning prescriptive, communal, and habitual perspectives for teachers to impart knowledge, skill, and values/attitudes successfully. This alignment may balance the quality of the AGRIS South African curriculum.